Investigating the Association Between Labour Epidural Analgesia and Postpartum Depression: A Prospective Cohort Study. Issue 2 (24th June 2021) - Tan, C.W.; Sultana, R.; Kee, M.Z.L.; Meaney, M.J.; Sng, B.L.
Abstract : ( Eur J Anaesthesiol . 2020;37:796–802) Approximately 10-15% of women worldwide experience postpartum depression (PPD) following childbirth, which can lead to suicidal behaviors, infanticide, decreased maternal cognitive function and even increased behavioral problems in children. Given the incidence of and morbidity associated with PPD, recent efforts have focused on identifying modifiable risk factors that may contribute to the development of PPD. The primary aim of this study was to determine whether an association exists between the use of epidural analgesia (EA) during labor and the development of PPD.